Jejunal Intussusception: A Rare Presentation of Carcinoid Tumor - Umashankkar Kannan; Amir A. Rahnemai-Azar; Ashish N. Patel; Vinaya Gaduputi; Ajay K. Shah (Case Reports in Surgery)
A 55-year-old male presented to the emergency department with sudden onset of diffuse abdominal pain for one day. Physical examination was remarkable for tenderness in the umbilical region. A CT scan of the abdomen showed intussusception involving the jejunum without any mass. The patient then underwent an exploratory laparotomy. During surgery, the distal jejunum was intussuscepted with mesenteric lymphadenopathy. Liver showed nodular deposits in both lobes of the liver. The involved small bowel segment was resected with primary anastomosis and liver was biopsied. Pathological examination showed multifocal deposits of well-differentiated carcinoids in the jejunum. The liver and mesenteric deposits were positive for metastatic carcinoid. Patient recovered well without any complications.